Effect of Counting Solution and Antihistaminics on Platelet Volume - Herrmann, R. G; Griggs, V. G (Thrombosis and Haemostasis, 1967)
A simple and rapid method is described for counting platelets with the Model F Coulter Counter. It was observed that platelet volume may be affected by the counting solution (CS) used. It was found that platelet swelling due to water entering the cell was related to the Na+ and K+ concentration in the CS. A simple CS (0.1455 NaCl, 0.002 M potassium oxalate) was found in which the platelets did not change in size. Two out of 5 antihistaminics tested produced platelet swelling. This phenomenon was unrelated to antihistaminic potency nor does it appear to be related to platelet aggregation. The normal rabbit median platelet volume was found to vary slightly from one rabbit to the next ranging between 3.58 to 4.76 µ3 with an average of4.11 µ3±0.15 (S. E.).